New International Calibration Standard (ICS-A1) for HPLC Analysis of Alpha-Acids in Beer: Submitted on behalf of the International Hop Standards Committee - Biendl, Martin; Foster, Bob (BrewingScience, 2019)
The International Hop Standards Committee (IHSC) announces the release of a new calibration standard, ICS-A1, for the HPLC analysis of alpha-acids in beer.